SAT0295 Comparison of subclinical carotid atherosclerosis in patients with psoriatic arthritis, psoriasis alone and controls. (23rd January 2014) - Magro-Checa, C.; Orgaz-Molina, J.; Rosales-Alexander, J.L.; Salvatierra, J.; Arias-Santiago, S.; Cantero-Hinojosa, J.; Ruiz-Carrascosa, J.C.; Raya-Άlvarez, E.
Abstract : Background: Patients with psoriatic arthritis (PsA) and cutaneous psoriasis alone (PsC) are known to have an increased risk of Cardiovascular (CV) disease. The increase of Carotid Intima-Media Thickness (cIMT) in patients with PsA and PsC has been demonstrated in several studies and serve as surrogate measure for cardiovascular diseases. However, there are no studies so far comparing the extent of subclinical atherosclerosis among them and with controls. Objectives: Our aim was to compare the prevalence of subclinical atherosclerosis, as measured by cIMT, between patients with PsA, PsC alone and controls. Methods: This cross-sectional study included 77 consecutive PsA patients who fulfilled the CASPAR criteria, compared to 77 patients with PsC and 77 age and sex matched controls. Patients with a previous CV event and diabetics were excluded. Inflammatory arthritis in PS patients was excluded by a rheumatologist in our outpatient clinic. Measurement of cIMT was performed using the Esaote MyLab25Gold Cardiovascular ultrasound machine and an automated edge detection software (QIMT). Presence of atherosclerotic plaques and the highest value of cIMT were recorded. A one way ANOVA was performed to analyze the statistical difference of cIMT between groups. Furthermore, multivariate regression analysis was used to adjust for the following variables: sex, age, body mass index, classic CV risk factors, lipid profile, duration in months since diagnosis of PsA and PsC, clinical patterns of the PsA and PsC, treatment, activity of the disease, and inflammatory markers (p<0, 05 was considered significant). Results: The mean age of all the patients was 47, 27±11, 39 (mean ± standard deviation) and48, 1% were females. The mean of the cIMT in the group of PsA was 659±118 microns and 8 pts (10, 4%) presented atheroscletoric plaques. The mean for the cIMT calculated in PS patients was 648±102 microns, and plaques were present in 9 patients (11, 7%). In the group of healthy controls, the mean was 614±96 microns, and plaques were seen in 2 patients (%). Statistical difference of cIMT intergroup was significant (p=0, 02). Multivariate regression analysis showed that the most important prognostic factors for predicting the cIMT in the PsA pts were the age and the CRP (p<0, 05). Variables associated with subclinical atherosclerosis in PsC pts included age, sex and total cholesterol level (<0, 05) and in the group of healthy controls the age. Clinical patterns of the PsA and Psoriasis, treatment and activity of the disease were not associated with atherosclerosis. Conclusions: cIMT and prevalence of atherosclerotic plaques are increased in pts with PsA and PsC compared with healthy controls.Although pts with PsA presented a greater cIMT than matched pts with PsC the prevalence of plaques was similar in both groups. References: Gonzalez-Juanatey C et al. High prevalence of subclinical atherosclerosis in psoriatic arthritis patients without clinically evident cardiovascular disease or classic atherosclerosis risk factors. Arthritis Rheum. 2007;57:1074-80. Disclosure of Interest: None Declared